2012
DOI: 10.1007/s10439-012-0530-7
|View full text |Cite
|
Sign up to set email alerts
|

Head Impact Exposure in Youth Football

Abstract: The head impact exposure for athletes involved in football at the college and high school levels has been well documented; however, the head impact exposure of the youth population involved with football has yet to be investigated, despite its dramatically larger population. The objective of this study was to investigate the head impact exposure in youth football. Impacts were monitored using a custom 12 accelerometer array equipped inside the helmets of seven players aged 7–8 years old during each game and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
178
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(193 citation statements)
references
References 31 publications
14
178
1
Order By: Relevance
“…In addition to the HITS device, researchers have implemented a 6DOF device 31,85 (n ¼ 2) or used the 6DOF with the standard HITS device 26,50,86 (n ¼ 3). The 6DOF device is part of the HITS and fits within Riddell Revolution (BRG Sports) helmets.…”
Section: Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the HITS device, researchers have implemented a 6DOF device 31,85 (n ¼ 2) or used the 6DOF with the standard HITS device 26,50,86 (n ¼ 3). The 6DOF device is part of the HITS and fits within Riddell Revolution (BRG Sports) helmets.…”
Section: Devicesmentioning
confidence: 99%
“…26 Recently, the STAR rating expanded to include ice hockey helmets. 114 In addition, the results of youth football studies 85 led the Pop Warner Little Scholars, Inc, youth football program to change to practice regulations that reduced head-impact exposure by 50%, 83 and high schools 115 and colleges 110 have begun to evaluate contact-practice regulations. Most notably, the Ivy League eliminated full-contact practices during the regular season starting in 2016.…”
Section: Clinical Utilitymentioning
confidence: 99%
“…The necks and torsos of young athletes are weaker than those of older individuals and, consequently, less force is required to cause brain injury. The developing brain might also be particularly vulnerable to axonal damage caused by the shearing forces of head trauma, which, in youth American football, can exceed linear acceleration forces of 100 g. 9 However, the average forces sustained in youth sports will generally be smaller than at higher levels of sport.…”
Section: Susceptibility and Resilience Of Young Brainsmentioning
confidence: 99%
“…[6][7][8][9][10] Neuroimaging and electrophysiological studies have identified structural and functional abnormalities in former contact sport athletes many years after they stopped playing. [11][12][13][14][15] Tackle football players ages 7-12 may experience hundreds of repetitive head impacts (RHI), concussive and/or subconcussive, over the course of one season, several of which may exceed forces of 80 g. 16,17 Our previous research suggests that incurring RHI during critical periods of neurodevelopment in childhood may lead to later-life mood, behavioral, and cognitive impairment. 18,19 However, the impact of RHI incurred during youth on later-life brain structure has not yet been systematically examined.…”
Section: Introductionmentioning
confidence: 99%